Infectious complications after primary total arthroplasty of the hip and knee joints - Vyrva, Oleg; Burlaka, Victor; Malyk, Roman; Ozerov, Konstantyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2011)
The article analyses problems in treatment of infectious complications after primary total hip and knee joint arthroplasty in 50 clinical cases. Risk factors, terms of development, volumes of lesion and wound flora in the above patients, who survived primary hip and knee joint arthroplasty and underwent treatment at the Institute, were analysed. It was proved that a favourable outcome in the treatment of such complications was possible with keeping to principles of early surgical tactics, adequate prolonged antibiotic therapy and thorough postoperative monitoring of such patients.